Corporate debt policy of small firms: An empirical (re)examination - Esperança, J. P.; Gama, A. P. M.; Gulamhussen, M. A. (Journal of Small Business and Enterprise Development, 2003)
The capital structure decision can be considered a difficult problem for academics as well as for managers. Corporate debt policy has been studied in the context of both large and small firms in developed countries, but comparatively less developed countries have received much less attention in the literature. This is particularly true in the case of medium income economies with an above average weight of financial intermediaries. This paper tests the factors affecting the capital structure decision of small firms in one such country. The pooled time series cross?section regression estimates for 995 firms and four years, suggests variables such as taxes, bankruptcy costs, size, collateral, age and growth opportunities affect the capital structure decisions of small firms. These findings have significant implications, both at the firm level and for the support of policies that redefine the financial infrastructure that may foster the emergence of local entrepreneurs in these economies.